Identifying patterns in city municipality incident reports by Lisbon citizens: A data-driven analysis - Sousa, Pedro Miguel Silva de (2024)
In a scenario of escalating urbanization, major cities face the challenge of providing optimal conditions for their residents. This work focuses on the significance of obtaining and analysing information regarding urban occurrences, as such knowledge is crucial in forecasting occurrences and efficiently allocating municipal resources. The primary objective of this dissertation is to provide data and forecasts that can empower municipal authorities to make informed decisions and proactively manage critical areas of the city. The research is based on data collected through the “Na Minha Rua” application, made available by the Lisbon City Council. By exploring this source of information, the aim is to identify patterns in urban occurrences, mapping areas prone to specific issues. This study seeks to contribute to a more effective approach in urban management, enabling the anticipation of needs and the implementation of preventive measures. By addressing urban dynamics through data analysis, this work offers valuable insights for optimizing the safety and quality of the urban environment. By understanding and anticipating incidents, municipal authorities can enhance their response, thus promoting a safer and more efficient city. This work represents a contribution to an informed and proactive approach to urban management, aiming to improve the quality of life for citizens in the city of Lisbon.